Palmatine Protects Against MSU-Induced Gouty Arthritis via Regulating the NF-κB/NLRP3 and Nrf2 Pathways - Cheng JJ; Ma XD; Ai GX; Yu QX; Chen XY; Yan F; Li YC; Xie JH; Su ZR; Xie QF (Dove Medical Press, 2022)
Juan-Juan Cheng,1 Xing-Dong Ma,1 Gao-Xiang Ai,1 Qiu-Xia Yu,2 Xiao-Ying Chen,1 Fang Yan,3,4 Yu-Cui Li,1 Jian-Hui Xie,3,5,6 Zi-Ren Su,1 Qing-Feng Xie3,4 1School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China; 2The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People's Republic of China; 3The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People's Republic of China; 4Li Ke and Qi Yu-ru Academic Experience Inheritance Studio, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, 510006, People's Republic of China; 5State Key Laboratory of Dampness Syndrome of Chinese Medicine, the Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People's Republic of China; 6Guangdong Provincial Key Laboratory of Clinical Research on Traditional Chinese Medicine Syndrome, Guangzhou, 510120, People's Republic of ChinaCorrespondence: Qing-Feng Xie; Zi-Ren Su, Email xieqingfeng1@gzucm.edu.cn; suziren@gzucm.edu.cnPurpose: Gouty arthritis could be triggered by the deposition of monosodium uric acid (MSU) crystals. Palmatine (PAL), a protoberberine alkaloid, has been proven to possess compelling health-beneficial activities. In this study, we aimed to explore the effect of PAL on LPS plus MSU crystal-stimulated gouty arthritis in vitro and in vivo.Methods: PMA-differentiated THP-1 macrophages were primed with LPS and then stimulated with MSU crystal in the presence or absence of PAL. The expression of pro-inflammatory cytokines and oxidative stress-related biomarkers and signal pathway key targets were determined by ELISA kit, Western blot, immunohistochemistry and qRT-PCR, respectively. In addition, the anti-inflammatory and antioxidant activities of PAL on MSU-induced arthritis mice were also evaluated.Results: The results indicated that PAL (20, 40 and 80 μM) dose-dependently decreased the mRNA expression and levels of pro-inflammatory cytokines (interleukin-1beta (IL-1β), IL-6, IL-18 and tumor necrosis factor alpha (TNF-α)). The levels of superoxide dismutase (SOD) and glutathione (GSH) were remarkably enhanced, while the level of malondialdehyde (MDA) was reduced. Western blot analysis revealed that PAL appreciably inhibited NF-κB/NLRP3 signaling pathways through inhibiting the phosphorylation of p-65 and IκBα, blocking the expression of NLRP3, ASC, IL-1β and Caspase-1, as well as enhancing the antioxidant protein expression of Nrf2 and HO-1. In vivo, PAL attenuated MSU-induced inflammation in gouty arthritis, as evidenced by mitigating the joint swelling, and decreasing the productions of IL-1β, IL-6, IL-18, TNF-α and MDA, while enhancing the levels of SOD and GSH. Moreover, PAL further attenuated the infiltration of neutrophils into joint synovitis.Conclusion: PAL protected against MSU-induced inflammation and oxidative stress via regulating the NF-κB/NLRP3 and Nrf2 pathways. PAL may represent a potential candidate for the treatment of gouty arthritis.Keywords: palmatine, NF-κB/Nrf2 signal pathways, NLRP3 inflammasome, gouty arthritis